Integrating Climate Basics, Climate Information Service, Climate Risk Management and Climate Smart Agriculture into the undergraduate agriculture Curriculum in Ethiopian Higher Education - Dejene, Sintayehu W.; Terefe, Tadesse; Belay, Berhanu; Amha, Yosef; Ambaw, Gebermedihin; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture contributes about 40% to the country’s GDP, more than 75% to employment, and 80% to foreign exchange earnings of the Ethiopia’s economy. However, climate change poses a serious risk to the sector. On the other hand, agriculture is a major contributor (i.e., about 55%) of the country’s greenhouse gas emission. To address the strong and bidirectional interrelationships between climate change and agriculture, the agricultural sector needs to transform in a climate-smart way. Climate change education will have paramount importance for tackling the problems associated with climate change through generating climate smart technologies for the enhancement of sustainable agricultural production and biodiversity conservation. Climate Change Educations (CCE) and trainings have long been recognized by the national CCE strategy (2017-2030), United Nations Framework Convention on Climate Change, the Paris Climate Change Agreement, and the Sustainable Development Goals of the United Nations (Agenda 2030) as key tools to unravel the complex and multi-sectoral challenges induced/posed by climate change. Thus, specifically, including the concepts of Climate Information Service (CIS) Climate Risk Management (CRM) and Climate smart agriculture (CSA) in the existing climate related courses is critical to build climate resilient agricultural sector in Ethiopia. Thus, Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) in collaboration with Ethiopian Higher Educations initiated to integrate the concept of CIS and CSA in the agricultural program in Ethiopia. Therefore, this document, explore if there is a gap between climate related course contents and the current CIS, CRM and CSA knowledge and innovations to addresses climate related agricultural challenges in ten undergraduate agricultural curricula of Ethiopian Higher Education Institutes. Ten climate related course descriptions were content analyzed to analyze gaps related to the concepts of CIS, CRM and CSA. The study found that there were gaps between the current curriculum and the desired knowledge and innovation of CIS, CRM and CSA to addresses the current and emerging climate change challenges in the agricultural sector. These results emphasize the need for curriculum review and reform to ensure CIS, CRM and CSA knowledge and innovations equipping the university graduates with comprehensive knowledge of climate change.